Comparison study between hydrothermal and coprecipitation method for green synthesize of magnetic silver nanoparticles - Abdullah, Mohammad Aiman Hakim; Abdul Aziz, Ainul Husna; Engliman, Nurul Sakinah (IIUM Press, 2024)
Nanoparticle research has been attractive for the past decade due to its unique electronic, mechanical, optical, chemical, and magnetic properties, which can be used in various applications, including sensors, medical, food, and others. Yet, the use of toxic chemicals in the synthesis of nanoparticles limits their potential use in the medical and food industries. The green synthesis of nanoparticles is eco-friendly and well-suited for many applications. However, there are some issues related to it as there are limited comparisons made between nanoparticles synthesized through different routes, and even the physiochemical and morphological properties are also not compared. Therefore, this study attempts to synthesize magnetic silver nanoparticles using the greener technique, which utilized the banana peel waste extract as the reductant during the synthesis of nanoparticles. The banana peel waste extract and the nanoparticles were characterized using a UV-VIS spectrometer, Fourier transform infrared spectroscopy (FTIR), and field emission scanning electron microscope (FESEM) to analyze the properties of the extract and the fabricated nanoparticles. The results found that the -OH group was present in both banana peel extract as well and the synthesis of silver nanoparticles in FTIR analysis, which is believed to come from the phenolic group that helps in the reduction of silver ions to silver nanoparticles during the synthesis process. VSM analysis indicates that the synthesized silver nanoparticles had ferromagnetic properties of 2.83 emu/g for the coprecipitation method and 3.91 emu/g for a hydrothermal method, which is considered stronger to be utilized for further application. In addition, FESEM analysis shows that the hydrothermal could synthesize the uniformly distributed and mono-dispersed spherical shape compared to the coprecipitation method, which produces uneven shapes like rods, pellets, and spheres. The study concludes that the green-synthesized silver nanoparticles using banana peel waste extracts could produce medium-strength magnetic silver nanoparticles, especially through a hydrothermal process when the diluted precursor ions were used compared to concentrated ones.